Effect of Acacia melanoxylon wood density on papermaking potential - Delgado, C. (2014)
In this work we study the behaviour in kraft cooking and papermaking of 6 Acacia melanoxylon wood chip samples, with basic densities of 449, 489, 493, 505, 514 and 616 kg/m3. The wood chip samples were screened and submitted to the kraft cooking process. Experiments were carried out with 1000-g o.d. of wood in a forced circulation digester. The cooked chips were disintegrated, screened and washed. The screened and total yields, kappa number and pulp viscosity were determined according to the standard methods. The morphological properties of pulp fibres were determined by image analysis of a diluted suspension in a flow chamber in Morfi®. The unbleached kraft pulps were submitted to a bleaching D0E1D1E2D2 sequence and their papermaking potential evaluated. The pulps were beaten in a PFI mill at 500, 2500 and 4500 revolutions under a refining intensity of 1.7 N/mm. Paper handsheets were prepared according to the Scan standard and tested regarding structural, mechanical and optical properties. Regarding the pulping potential, the pulp yield ranged between 47.7 and 57.7%. The selected wood samples provided bleached kraft pulps with markedly different biometrics characteristics. In fact, the mean values of fibre length, fibre width and coarseness ranged between 0.77 and 0.98 mm, 17.8 and 19.4 μm, 4.8 and 6.2 mg/100m, respectively. As expected, these biometrics characteristics have very high impact on paper structure, including smoothness, and on mechanical and optical properties, for the unbeaten pulps. At a given beaten level, the differences between pulps remain very high. Moreover, for a given paper density, tensile and tear strength, and light scattering coefficient are significantly different. To reach a given paper density, however, the different pulps required very different energy consumptions in beating.